Hubungan Kompetensi Bidan dalam Continuity of Care dengan Tingkat Keberhasilan Persalinan Fisiologis - Norma Safitri; Warda M; Nell Mana Baru; Cakrawati R; Rezqiqah Aulia Rahmat (Barongko: Jurnal Ilmu Kesehatan, 2026)
Background: Physiological labor is an ideal, normal delivery process without complications. However, its success is greatly influenced by the quality of midwifery care. The concept of Continuity of Care (CoC) emphasizes the provision of continuous care from pregnancy, labor, and postpartum. Midwive’s competence in implementing CoC is believed to influence the success of physiological labor. Objective: This study aims to analyze the relationship between midwives' competence in Continuity of Care and the success rate of physiological labor. Methods: This study used an observational analytical design with a cross-sectional approach. The sample consisted of 100 pregnant women assisted by midwives at primary health facilities in District X, selected using purposive sampling. Midwives' competence was measured using a valid and standardized questionnaire, while the success of physiological labor was recorded based on medical records. Data were analyzed using the Chi-Square test and logistic regression. Results: The results showed a significant relationship between midwives' competence in Continuity of Care and the success of physiological labor (p < 0.01). Pregnant women cared for by midwives with high competence were 3.2 times more likely to experience a physiological birth than those cared for by midwives with low competence (OR = 3.2; 95% CI = 1.6–6.4). Conclusion: Midwive’s competence in implementing Continuity of Care positively influences the success of a physiological birth. Improving midwives' competence through training and coaching is an important strategy to support safe and physiological births.